KARAKTERISASI TEBAL LAPISAN BATAS FLUIDA NANO ZrO2 DI PERMUKAAN PEMANAS PADA PROSES PERPINDAHAN PANAS KONVEKSI ALAMIAH - Wardhani, Veronica Indriati Sri; Rahardjo, Henky P. (Jurnal Teknologi Reaktor Nuklir Tri Dasa Mega, 2015)
CHARACTERIZATION of boundary layer thickness OF nano FLUID ZrO2 on natural convection process. Cooling system is highly influenced by the process of convection heat transfer from the heat source to the cooling fluid. The cooling fluid usually used conventional fluid such as water. Cooling system performance can be improved by using fluids other than water such as nano fluid that is made from a mixture of water and nano-sized particles. Researchers at Batan Bandung have made nano fluid ZrO2 from local materials, as well as experimental equipment for studying the thermohidraulic characteristics of nano fluid as the cooling fluid. In this study, thermohidraulic characteristics of nano fluid ZrO2 are observed through experimentation. Nano fluid ZrO2 is made from a mixture of water with ZrO2 nano-sized particles of 10-7-10-9 nm whose concentration is 1 g/ltr. This nano fluid is used as coolant in the cooling process of natural convection. The natural convection process depends on the temperature difference between heat source and the cooling fluid, which occur in the thermal boundary layer. Therefore it is necessary to study the thermal boundary layer thickness of nano fluid ZrO2, which is also able to determine the local velocity. Experimentations are done with several variation of the heater power and then the temperature are measured at several horizontal points to see the distribution of the temperatures. The temperature distribution measurement results can be used to determine the boundary layer thickness and flow rate. It is obtained that thermal boundary layer thickness and velocity of nano fluid ZrO2 is not much different from the conventional fluid water.